Neural networks for gas turbine engine diagnosing - Якушенко, О.С. (Proceedings of National Aviation University (archive), 2004)
Problems of a neural networks architecture definition, which is optimal one for effective gas turbine engine technical state class recognition by parameters of working process, are considered in article. The question of formation of recognition quality criteria and creation of data sets for the network training and testing are considered too.